Bot mitigation – how gapsin understanding and ownership are exposingbusinesses to greater threats. Issue 11 (November 2020) - Still, Andy
Abstract : When people think of security, there is a tendency to think of building high walls around what needs to be protected. Thieves are, after all, opportunists, and if a target can look too tricky to breach then they will look elsewhere for an easier score. This is no longer true of cyber security. The poor security of other businesses is no longer your advantage – it's now your problem. When people think of security, there is a tendency to think of building walls around what needs to be protected. Thieves are opportunists, and if a target looks too tricky, they will go elsewhere. But this is no longer true of cyber security. The poor security of other businesses is no longer to your advantage – it's now your problem. Using credentials stolen elsewhere, bots are probing your defences looking for weaknesses such as password reuse. Without a deep understanding of how bots operate, companies are putting themselves at risk, argues Andy Still of Netacea.